SARS-CoV-2 vaccination and myocarditis in a highly vaccinated New Zealand population. (3rd October 2022) - Greer, C; Daly, M; Troughton, R; Adamson, P D
Abstract: Background: A higher incidence of myocarditis has been reported in those who have recently received mRNA SARS – CoV-2 vaccination.1 Canterbury District Health Board (CDHB) serves 578, 290 people, including 441, 852 adults, with one large tertiary referral hospital offering specialist cardiology services. In 2021 97% of eligible adults received at least one dose and 92% two doses of the BNT162b2 mRNA vaccine (Pfizer-BioNTech). During this time only 21 community cases of COVID-19 infection were reported. We investigated the incidence of myocarditis during the BNT162b2 mRNA vaccine rollout in comparison to the preceding 5 years assuming a stable population size. Methods: All adult patients admitted to our hospital who received a diagnostic code of acute myocarditis (ICD10 codes I40, I41 and I51.4) during admission between 2016 and 2021 were included. Demographics and peak troponin concentration (hsTnI) were recorded. Vaccine-associated myocarditis was defined as that leading to admitted within 28 days of BNT162b2 vaccination. Myocarditis-associated mortality was defined as death occurring within 28 days of hospital admission. Incidence of myocarditis before and during COVID-19 vaccination was tested using ANOVA. Results: Between 2016 and 2020 there were 178 total hospital admissions (annualised mean 35.6 [SD6.3] range 28–44) with myocarditis. The mean age was 47.8 [SD15.9] years, 38% were women, and median peak hsTnI 641 (IQR 95.25–8526) ng/L. One patient died within 28 days of admission. In 2021 there were 43 myocarditis admissions, mean age 49.7 [SD18] years, 42% women, with a median hsTnI 355 (IQR 106.5–1876.5) ng/L. Nine of these admissions were within 28 days of vaccination. They were 78% female, mean age 52.6 [SD24.8] years, median peak hsTnI 179 (IQR 52–528) ng/L. One patient died during admission. There was no variance in annual incidence of myocarditis during vaccine rollout (p=0.342). Conclusion: In a highly vaccinated adult population largely free of COVID-19 infection there were few cases of myocarditis within 28 days of vaccination and no increase in incidence overall compared to the preceding 5 years. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Heart Foundation of New Zealand grant to C Greer